Education, Participation and Disparity A Descriptive Picture of the State of Jammu and Kashmir - Naresh Kumar,; Hazra, Sonali (JOURNAL OF INDIAN EDUCATION, 2017)
The descriptive picture of the educational participation helps to identify gaps which need to be filled by appropriate policy. National Sample Survey maps the participation of the population within the age group of 5–29 years, thereby inviting state-specific initiatives to overcome the hindrances. The State’s strength lies in the huge demographic dividend which has almost remained unexplored in the absence of innovative policies and programmes. Untapped youth dividend often poses a challenge and demand resource investment for a longer period. One important investment which every State has to plan very prudently is for the educational participation and completion of the children. The paper takes cognizance of these concerns and provides the descriptive picture of the educational participation in the State of Jammu and Kashmir. It points to the fact that educational participation in the State has seen unparallel growth on social, gender and regional lines. The private unaided schools are the popular choice among the urban parents, while government schools usually cater to the rural demand. The household expenditure which has been relatively higher for the State would be a possible obstacle to improve the rural participation in education. Financial constraints have been identified as the prominent factor for discontinuation. The paper invites state initiatives to address factors of the non-enrolment vis-à-vis discontinuation which has peculiar nature in rural and urban area.